STRATEGI PENGELOLAAN DAN PENGEMBANGAN HUTAN KOTA MUHAMMAD SABKI KOTA JAMBI - M. Bayu Dwi ramahdan (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2026)
Grellen Open Space plays a crucial role in designing a sustainable city. This study aims to analyzel and formulatel strategiels for the management and development of the Muhammad Sabki City Forest in Jambi City. The Muhammad Sabki City Forest, which covers an area of approximately 10.56 hectares, not only plays a role in providing comfortable public space but also in maintaining ecosystem balance and providing social and educational benefits to the community. This research was conducted in the Muhammad Sabki City Forest, Kelnali Asam Bawah, Jambi City. Data collection techniques included interviews, observation, and documentation. The study used a purposive sampling method for collecting respondents, with data analyzed using a SWOT analysis. The results showed that the analysis of internal and external environmental factors, including the strategy for managing and developing the Muhammad Sabki City Forest in Jambi City, demonstrated that the internal factor score was 2.59, while the external factor score was 2.62. The SWOT analysis revealed a quadrant point in the diagram positioned in quadrant I, namely SO (strengths and opportunities) or Aggressively Strategically (Profitably). The focus of this strategy is to utilize internal strengths to maximize existing opportunities, thus supporting an aggressive growth policy.